PENGARUH PUBLICNESS TERHADAP HUBUNGAN ANTARA PARTISIPASI PEMBUATAN ANGGARAN DENGAN KINERJA MANAJERIAL - Alliyah, Siti (potensio, 2012)
This study aims to examine the the relationship between participation in budget making andmanaging performance. Results obtained from these studies have been done was not consistentand there was a contradition between one researcher to another. This study provides empiricalevidence about the effect of publicness on the relation between participation in budgetmakingand managing performance in universities and hospitals both public and private. Sothat the budget can serve as a control, when compiling the budget should be noted that theparties involved in preparing the budget. One is that managers are directly responsible formanaging performance in a public or private organizations. The sampling method used waspurposive sampling. In this study, sample criteria are the managers who are at level two intheir respective institutions. In the 70 private sector organizations and the public sector is 50.From the results of the study concluded that there are significant relationship betweenparticipation publicness in budget making and managing performance.Key word: publicness, participation, and managerial performace